2015
DOI: 10.1016/j.cnsns.2014.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the regulatory system for diabetes mellitus with a threshold window

Abstract: Please cite this article as: Yang, J., Tang, S., Cheke, R.A., Modelling the regulatory system for diabetes mellitus with a threshold window, Communications in Nonlinear Science and Numerical Simulation (2014), doi: http:// dx.doi.org/10.1016/j.cnsns. 2014.08.012 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Up to date, a wide range of mathematical model are investigated, which are categorized into either subcutaneous or intravenous model. Some of it is composed of partial differential equations, 22 ordinary differential equation, 23,24 delayed differential equations and so on. 25 In this work, an intravenous patient model, widely known as Bergman's minimal model, is considered, which is mostly referenced as intravenous glucose tolerance test (IGVTT) model in the literature.…”
Section: Patient Modelmentioning
confidence: 99%
“…Up to date, a wide range of mathematical model are investigated, which are categorized into either subcutaneous or intravenous model. Some of it is composed of partial differential equations, 22 ordinary differential equation, 23,24 delayed differential equations and so on. 25 In this work, an intravenous patient model, widely known as Bergman's minimal model, is considered, which is mostly referenced as intravenous glucose tolerance test (IGVTT) model in the literature.…”
Section: Patient Modelmentioning
confidence: 99%
“…During the past decades, a variety of mathematical models have been proposed to describe the dynamics of the glucose–insulin interactions including ordinary differential equations [25, 26], partial differential equations [27], and delayed differential equations [28]. In this paper, the following minimal model of the insulin–glucose regulatory system is used to design suboptimal insulin injection rules for T1D patients.…”
Section: Mathematical Model Of Type 1 Diabetesmentioning
confidence: 99%
“…Moreover, the effect of physical exercise on the dynamics of glucose and insulin has been investigated [30], thus it is interesting to show how does this affects the dynamics if we put this into our proposed models. Recently, non-smooth dynamic systems or Filippov systems have been applied widely in many fields of science [31][32][33], as a result, the dynamical behaviors of the glucose-insulin system could be investigated more clearly once we consider such models. Consequently, to address these with the aim of improving strategies for the treatment of diabetes, such research is planned for the near future and will be reported elsewhere.…”
Section: A C C E P T E D Mmentioning
confidence: 99%